Training in Pediatric Gastrointestinal Endoscopy during Surgery Residency: Can Training Programs Currently Educate Proficient Pediatric Endoscopists? A Nationwide Assessment - Giovanni Parente; Marco Di Mitri; Tommaso Gargano; Mario Lima (Gastrointestinal Disorders, 2023)
Background: Technological advances in pediatric gastrointestinal (GI) endoscopy require highly specialized physicians. Therefore, proper training is fundamental. The aim of this study was to assess the level of competence of pediatric surgery residents to determine areas that should be addressed to design better training programs focused on pediatric GI endoscopy. Methods: An observational study was performed on all Italian pediatric surgery trainees that concluded the training program by the end of 2021, who were asked to answer a questionnaire about the quality of the GI endoscopy education received during their 5 years of residency. Results: 12 out 14 (86%) pediatric surgery trainees answered the questionnaire. A total of 50% (6/12) of the trainees declared they were interested in pediatric GI endoscopy, and 42% (5/12) said that they would be interested in dedicating themselves to this discipline in the future. Only 33% (4/12) of them were in a center equipped with endoscopy simulators. Among them, 17% (2/12) never took part in GI endoscopic procedures while working in centers in which GI endoscopy is performed exclusively by pediatric gastroenterologists, 25% (3/12) had never performed GI endoscopic procedures as a first operator and 17% (2/12) not even as assistant. Overall, 50% (6/12) were not satisfied with the level of education received and only 17% (2/12) declared that they felt confident enough to perform routine endoscopies alone. Conclusions: Our study highlights great inhomogeneity between different schools and some important failings. Better programs should be designed to educate proficient pediatric GI endoscopists.